The Influence of Nonpharmacological Complex Therapy Conducted at a Community Day-Care Center on Cognitive function and Mood in Older Adults - Gorzkowska A; Zacharska-Quaium I; Cholewa J; Cholewa J (Dove Medical Press, 2020)
Agnieszka Gorzkowska,1 Izabela Zacharska-Quaium,2 Joanna Cholewa,3 Jarosław Cholewa4 1Department of Neurorehabilitation, Faculty of Medical Sciences in Katowice, Medical University of Silesia, Katowice, Poland; 2Community Day-Care Center by Chance for Health Association in Golub-Dobrzyn, District Hospital, Golub-Dobrzyn, Poland; 3Department of Physical Education and Adapted Physical Activity, Institute of Physiotherapy and Health Sciences, The Jerzy Kukuczka Academy of Physical Education in Katowice, Katowice, Poland; 4Department of Health Related Physical Activity and Tourism, The Jerzy Kukuczka Academy of Physical Education in Katowice, Katowice, PolandCorrespondence: Jarosław CholewaDepartment of Health Related Physical Activity and Tourism, The Jerzy Kukuczka Academy of Physical Education in Katowice, Mikołowska 72A str, Katowice 40-065, PolandTel +48 601530011Fax +48 338542166Email j.cholewa@awf.katowice.plIntroduction: Nonpharmacological interventions in the elderly may lead to the reduction of cognitive and depressive symptoms. The aim of the study was to evaluate changes in cognitive functions and mood in older adults participating in therapy, conducted in the community day-care center (CD-CC).Patients and Methods: The study group (SG) included 46 elderly adults (21 M, 25 W), the control group (CG) included 45 adults (12 M, 33 W), who participated in the activities of the University of the Third Age. The following measuring tools were used: Mini-Mental State Examination, Clock-Drawing Test, Verbal Fluency Test, Digit Span Test, Stroop Color and Word Test, Beck’s Depression Inventory, and Hospital Anxiety and Depression Scale. The intervention consisted of CD-CC 6-month nonpharmacological therapy.Results: In the SG, compared to the CG, the scores on all the cognitive tests were significantly lower, Beck’s Depression Inventory was significantly higher. After intervention, the SG and the CG did not show substantial differences in their scores on the Mini-Mental State Examination, Clock-Drawing Test, and Beck’s Depression Inventory. In the SG, a significant improvement was reported on the Verbal Fluency Test, Beck’s Depression Inventory and Hospital Anxiety and Depression Scale scores.Conclusion: The CD-CC complex therapy can be helpful for cognitive and emotional elderly functioning.Keywords: cognition, depression, aging, elderly, community day-care center